Genomic characterization of Streptococcus suis serotype 31 isolated from one human and 17 clinically asymptomatic pigs in Thailand - Boueroy, Parichart; Phetburom, Nattamol; Duangjanchot, Rapeephan; Wongsurawat, Thidathip; Jenjaroenpun, Piroon; Chopjitt, Peechanika; Hatrongjit, Rujirat; Zheng, Han; Li, Jinquan; Kerdsin, Anusak (Veterinary microbiology, 2025)
Streptococcus suis is a zoonotic pathogen capable of causing severe diseases in humans and pigs. Frequently, S. suis serotype 31 strains have been isolated from pigs. The first human case of S. suis was reported in Thailand in 2015. In total, 18 strains from one human and 17 clinically asymptomatic pigs in Thailand were analyzed to characterize S. suis serotype 31. In total, 11 different STs were identified, with the major ST being ST2767 (38.89 %; 7/18). The minimum core-genome (MCG) classification revealed that almost all of the serotype 31 strains belonged to MCG7 (94.44 %; 17/18). Genomic analysis revealed that the serotype 31 isolates were major clusters with the porcine-healthy strains from China, Viet Nam, and Thailand. The human serotype 31 ST221 isolate was closely related to S. suis serotype 5 and 24 strains (CC221/234) isolated from Thailand. All serotype 31 strains were multidrug resistant with resistance to azithromycin (100 %; 18/18) and tetracycline (100 %; 18/18). Notably, 10 (55.56 %) of the serotype 31 strains were resistant to penicillin, while 8 strains (44.44 %) showed intermediate resistance to this agent. High substitutions were observed in three penicillin-binding proteins (1 A, 2B, and 2X) of these serotype 31 strains. The most prevalent antimicrobial resistance genes were erm(B) (100 %; 18/18) and tet(O) (66.67 %; 12/18). Overall, 7 strains carried integrative conjugative elements (ICEs) that harbored antimicrobial resistance genes, such as erm(B), tet(O), and tet(W). This study contribute to understanding the genomic diversity and provide valuable information for public health awareness of multidrug-resistant S. suis serotype 31. •Multilocus sequence typing showed that serotype 31 exhibited high heterogeneity with diverse sequence types (ST). In total, 12 different STs were identified, with the major ST being ST2767 (38.89 %; 7/18).•All serotype 31 strains were multidrug resistant with complete resistance to azithromycin (100 %; 18/18) and tetracycline (100 %; 18/18). Notably, 10 (55.56 %) of the serotype 31 strains were resistant to penicillin, while 8 strains (44.44 %) showed intermediate resistance to this agent.•Non susceptibility to penicillin with their mutations of PBP1A, PBP2B, and PBP2X proteins was detected in all strains.•This current study, S. suis serotype 31 strains showed multidrug resistance, with ICEs possibly being crucial in disseminating antibiotic resistance genes including erm(B), tet(O), tet(M), tet(W), ant(6)-Ia, aph(3′)-III, aac(6′)-aph(2''), lsa(E), optrA, and cat.•Our study should expand understanding of the S. suis serotype 31 genomic insight and should provide valuable information and greater awareness for its applicability in surveillance and prevention.